A feasibility study of operating a sheep dairy in central Iowa - Venard, Kathryn Lyn (Kansas State University, 2008)
The sheep dairy industry in the United States is small. Producers are concentrated in a few areas geographically with the greatest demand for sheep milk products located on the east and west coasts. The purpose of this analysis is to determine if a family-run sheep dairy located in Central Iowa could produce an annual profit of $40,000 without utilizing labor hired outside the family. Budgets were created and used to determine the revenues and costs of operating a sheep dairy, and producing and selling three different end products for sale: fluid milk, cheese and bars of soap. Microsoft Solver was used to determine the product mix that would maximize the total profit of the enterprise. The profit of the enterprise depends on a number of factors including the cost of feed, the number of ewes milked and the amount of milk each ewe produces. A maximum profit of $66,993 could be generated by selling 74% of the milk as fluid milk, 25% of the milk processed into cheese and 1% of the milk processed into soap. The diversification of products would help buffer the enterprise from volatility in the product markets. While the budgets show that this enterprise is profitable, local markets for these products must be identified and/or developed for the profits to be realized.
Keywords: Sheep; Milk; Dairy; Cheese; Iowa; Economics; Agriculture, Food Science and Technology (0359); Economics, Agricultural (0503); Economics, Finance (0508)